Święty Augustyn i tekst Pisma Świętego = Saint Augustine and the Bible text - Królikowski, Janusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Saint Augustine, whose influence is visible in terms of his approach to the Bible and Its interpretation, is a key figure of the Church and Western culture. He described his entire perspective on the Bible in his work "De doctrina christiana", which still deserves attention and a place among the contemporary interpretations of the Bible. Among the topics dealing with the text of the Bible, which Augustine discusses, the most significant are the questions of the truth and authority of the Septuagint, the canon of the Holy Scriptures, biblical inspiration and the spiritual interpretation of biblical texts as well as the qualities of Christian orator.
Keywords: Augustyn, św. (354-430); Septuaginta; kanon biblijny; natchnienie biblijne; interpretacja duchowa; mówca chrześcijański; kultura klasyczna; retoryka; Biblia; Bible; Septuagint; biblical canon; biblical inspiration; spiritual interpretation; Christian orator; classical culture; rhetoric